Profil risiko sindrom metabolik pada komunitas Majelis Taklim Nurul Hikmah Palembang - Nita Parisa; Masagus Irsan Saleh; Ziske Maritska; Bintang Arroyantri Prananjaya; Veny Larasati (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
The incidence of Metabolic Syndrome is 20-25% in the world and 13.13% in Indonesia. Metabolic syndrome is not a diagnosis but a collection of various symptoms that can develop into diseases or chronic conditions such as hypertension, hypercholesterolemia and diabetes mellitus (DM), which results in cardioserebrovascular disease. Metabolic Syndrome is more common in women than men. This community service is carried out at the request of the Taklim Assembly ladies Nurul Hikmah in the neighborhood of RW.15 Unsri lecturer’s residents, Bukit Lama, Ilir Barat 1 Palembang, mostly aged over 40 years. In this activity it was found that the majority of participants' awareness of the dangers of Metabolic Syndrome was still low. This is indicated by the number of participants who had excess body weight and waist circumference (44.29%), increased blood pressure (45.71%) and increased cholesterol levels (77.14%). The participants felt very helped and hoped that these community service activities or similar could be routinely carried out in the future.